ANALISIS FAKTOR YANG MEMPENGARUHI KEJADIAN DEMENSIA PADA LANSIA DI PANTI BHAKTI KASIH SITI ANNA TAHUN 2024 - Utari, Aulia; Kusumajaya, Hendra; Anggraini, Rima Berti (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2025)
Dementia is one of the global health problems whose prevalence continues to rise in line with the increasing number of elderly populations. This condition not only disrupts cognitive function, behavior, and social abilities but also has a significant impact on the quality of life of older adults. In addition, the economic and social burden caused by dementia is increasingly evident, particularly in developing countries such as Indonesia, which is currently experiencing a surge in the elderly population. One of the institutions accommodating elderly individuals with dementia symptoms is Panti Bhakti Kasih Siti Anna in Pangkalpinang. This study is therefore important to identify the factors influencing the incidence of dementia within that setting. The research focused on analyzing both risk factors and supporting factors that contribute to the occurrence of dementia among the elderly. The study employed a qualitative method with a phenomenological approach through in-depth interviews and documentation involving nurses, the head nurse, and elderly residents with dementia. The research was conducted from May 22 to May 30, 2024, using a non-probability sampling technique, specifically convenience sampling. The key stages included collecting primary data through interviews, observing the daily activities of the elderly, and conducting thematic analysis of risk factors such as age, level of knowledge, and physical activity, as well as supporting factors such as institutional policies, social support, and the availability of supporting facilities. The findings indicate that the informants’ understanding of dementia was relatively good, routine physical activity played an important role in maintaining cognitive function, and institutional support contributed significantly to the well-being of the elderly. In conclusion, knowledge-based interventions, structured activities, and strong social support are essential strategies to reduce the prevalence of dementia while enhancing the quality of life of elderly residents in the institution. ABSTRAKDemensia merupakan salah satu masalah kesehatan global yang prevalensinya terus meningkat seiring pertambahan jumlah penduduk lanjut usia. Kondisi ini tidak hanya mengganggu fungsi kognitif, perilaku, dan kemampuan sosial, tetapi juga berdampak besar terhadap kualitas hidup lansia. Selain itu, beban ekonomi dan sosial akibat demensia semakin dirasakan, terutama di negara berkembang seperti Indonesia, yang tengah menghadapi lonjakan populasi lansia. Salah satu institusi yang menampung lansia dengan gejala demensia adalah Panti Bhakti Kasih Siti Anna di Pangkalpinang. Penelitian ini penting dilakukan untuk mengidentifikasi faktor-faktor yang memengaruhi kejadian demensia di lingkungan tersebut. Fokus penelitian diarahkan pada analisis faktor risiko maupun faktor pendorong yang berperan terhadap munculnya demensia pada lansia. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan fenomenologi melalui wawancara mendalam dan dokumentasi terhadap perawat, kepala perawat, serta lansia dengan demensia. Penelitian dilakukan pada 22-30 Mei 2024 dengan teknik non probability sampling, khususnya convenience sampling. Tahapan penting meliputi pengumpulan data primer melalui wawancara, observasi aktivitas lansia, serta analisis tematik terhadap faktor risiko seperti usia, tingkat pengetahuan, dan aktivitas fisik serta faktor pendorong seperti kebijakan panti, dukungan sosial, dan ketersediaan fasilitas penunjang. Hasil penelitian menunjukkan bahwa pemahaman informan tentang demensia cukup baik, aktivitas fisik rutin berperan dalam mempertahankan fungsi kognitif, dan dukungan sistem dari panti memberikan kontribusi besar bagi kesejahteraan lansia. Simpulannya, intervensi berbasis pengetahuan, aktivitas terstruktur, dan dukungan sosial menjadi strategi utama untuk menekan prevalensi demensia sekaligus meningkatkan kualitas hidup lansia di panti.